Jobless growth in the Central and Eastern European countries - Onaran, Özlem (Amherst, 2008)
"This paper estimates a labor demand equation based on the panel data of manufacturing industry in the Central and Eastern European Countries (the Czech Republic, Hungary, Poland, Slovakia, Slovenia, Lithuania, Bulgaria, and Romania) in order to test the effect of domestic factors (wages and output) and international factors (exports, imports, and foreign direct investment) on employment during the era of post-transition recovery. The findings indicate that employment does not respond to wages in more than half of the cases. The output elasticity of labor demand is mostly positive, but low, with a number of cases where employment is completely de-linked from output. An impressive speed of integration to the European economic sphere through FDI and international trade has not prevented job losses in the manufacturing industry. While there are very few cases of positive effects, insignificant effects of trade and FDI dominate the findings with some evidence of negative effects as well"